Effect of micro-particles on rough surface spur gears under TEHL with non-Newtonian lubricant - Mongkolwongrojn MONGKOL; Panichakorn JESDA (My University, 2016)
This paper presents the performance characteristics of rough surface spur gears under thermo-elastohydrodynamic lubrication (TEHL) with non-Newtonian solid-liquid lubricant based on a Power law viscosity model. The bi-phase lubricant contains oil with Molybdenum disulfide particles. The time dependent modified Reynolds equation, elasticity equation, powder load carrying capacity, and energy equation with initial conditions were formulated and solved numerically using a multigrid multilevel with full approximation technique for an involute spur gear. In this analysis, the normal load and overloads are applied on either two pairs or one pair of gear teeth respectively. The transitions from two pairs to one pair and vice versa are modeled as a step variation of load. The effects of solid particle concentration, diameter of solid particle and surface roughness were examined in the region along the line of action of the meshing gear. The results show that both solid particle concentration and surface roughness affect significantly the film thickness, film temperature and friction coefficient, but the diameters of solid particle are relatively insignificant for rough TEHL.
Keywords: Particle (ecology); Gear and Bearing Dynamics Analysis